Outcome of mentorship programs based on six specific criteria of registered nurses in Malaysia - Mohamed Ludin, Salizar (Lincoln University (Malaysia), 2019)
Background: Mentoring of new staff nurses is frequently performed. Internationally researches have reported that this exercise helped the new staff to retain information better, adopt a professional conduct, and be more satisfied with their jobs. Mentoring programmes are usually conducted to encourage cooperation as well as socialisation among the new registered nurses (RNs) in specific units or organisations. Aim: This research aims to evaluate the outcome of mentorship programs based on six specific criteria and nurses' willingness to stay in the profession in hospital settings. Method: A comparative cross-sectional study designed via convenience sampling was conducted in nine hospitals using the self-administered mentorship for nurses (MNMSN) questionnaire. Findings: A total of 593 respondents were recruited, mostly female (87.6%), under 25 years old (84.7%), from Malay (71%) and highest nursing education of diploma level (99.2%). The predisposing factors that influence performance for pre- and post-program are 'patients assessment' (mean=4.763, S.D.=0.52 and mean=4.733, S.D.=0.536); 'clinical decision' (mean =4.722, S.D=0.527 and mean=4.73, S.D.=0.54); 'cultural competencies' (mean=4.42, S.D.=0.443 as well as mean=4.354, S.D=0.442); and 'professionalism' (mean=4.764, S.D.=0.533 and mean=4.698, S.D.=0.563) respectively. Each predisposing factor showed a significant correlation (strong and moderately positive). Overall result for 'willingness to stay' is significant [F, (5,585)=556.308, p<0.05] pre-program compared to post-program (willingness to stay is significantly correlated [F (5,585)=544.907, p<0.05]). Discussion: The mentorship program showed a positive transition among new nurses to start their nursing career. They somewhat agree with all statements regarding patient's assessment skill, clinical decision making, professionalism, positive feeling and willingness to continue working as a nurse. However, according to several nurses admitted, their cultural competency and sensitivity were somewhat low and challenging. Conclusion: Mentor-mentee programmes can improve new RNs' willingness to stay and increase retention. Nurses were able to face greater challenges to provide cultural and linguistically appropriate healthcare services. Therefore, guidance by the mentor should be given highest emphasis.